Sexual Health and Well-being Among Older Men and Women in England: Findings from the English Longitudinal Study of Ageing - Lee, David M.; Nazroo, James; O’Connor, Daryl B.; Blake, Margaret; Pendleton, Neil (Archives of sexual behavior, 2016)
We describe levels of sexual activity, problems with sexual functioning, and concerns about sexual health among older adults in the English Longitudinal Study of Ageing (ELSA), and associations with age, health, and partnership factors. Specifically, a total of 6,201 core ELSA participants (56 % women) aged 50 to >90 completed a comprehensive Sexual Relationships and Activities questionnaire (SRA-Q) included in ELSA Wave 6 (2012/13). The prevalence of reporting any sexual activity in the last year declined with age, with women less likely than men at all ages to report being sexually active. Poorer health was associated with lower levels of sexual activity and a higher prevalence of problems with sexual functioning, particularly among men. Difficulties most frequently reported by sexually active women related to becoming sexually aroused (32 %) and achieving orgasm (27 %), while for men it was erectile function (39 %). Sexual health concerns most commonly reported by women related to their level of sexual desire (11 %) and frequency of sexual activities (8 %). Among men it was level of sexual desire (15 %) and erectile difficulties (14 %). While the likelihood of reporting sexual health concerns tended to decrease with age in women, the opposite was seen in men. Poor sexual functioning and disagreements with a partner about initiating and/or feeling obligated to have sex were associated with greater concerns about and dissatisfaction with overall sex life. Levels of sexual activity decline with increasing age, although a sizable minority of men and women remain sexually active until the eighth and ninth decades of life. Problems with sexual functioning were relatively common, but overall levels of sexual health concerns were much lower. Sexually active men reported higher levels of concern with their sexual health and sexual dissatisfaction than women at all ages. Older peoples’ sexual health should be managed, not just in the context of their age, gender, and general health, but also within their existing sexual relationship.